A Caenorhabditis elegans model to study dopamine transporter deficiency syndrome. (2nd September 2016) - Illiano, Placido; Lanzo, Ambra; Leo, Damiana; Paglione, Maria; Zampi, Giuseppina; Gainetdinov, Raul R.; Di Schiavi, Elia
Abstract: Dopamine transporter deficiency syndrome (DTDS) is a novel autosomal recessive disorder caused by mutations in the dopamine transporter (DAT), which leads to the partial or total loss of function of the protein. DTDS is a pharmacoresistant syndrome and very little is known about its neurobiology, in part due to the lack of relevant animal models. The objective of this study was to establish the first animal model for DTDS with strong construct validity, using Caenorhabditis elegans, and to investigate the in vivo role played by DTDS‐related mutations found in human DAT (hDAT). We took advantage of a C. elegans knockout for the hDAT orthologue, ce dat‐1, to obtain genetically humanized animals bearing hDAT, in the wild type and in two mutated forms (399delG and 941C>T), in a null background. In C. elegans transgenic animals expressing the human wild‐type form, we observed a rescue of the knockout phenotype, as assessed using two well‐established paradigms, known to be regulated by the endogenous uptake of dopamine or 6‐hydroxydopamine (6‐OHDA) by DAT. The less severe mutation (941C>T) was able to partially rescue only one of the knockout phenotypes, whereas the 399delG mutation impaired DAT function in both phenotypic paradigms. Our in vivo phenotypic findings demonstrate a functional conservation between human and nematode DAT and validate previous in vitro indications of the loss of function of hDAT in carriers of DTDS‐related mutations. Taken together, these observations establish C. elegans as a novel animal model for fast and inexpensive screening of hDAT mutations in functional and in vivo tests. Abstract : Caenorhabditis elegans dopamine transporter (DAT) orthologue, ce dat‐1, maintains homeostasis in dopamine (DA) signalling. ce dat‐1 knockout (KO) causes accumulation of extracellular DA‐inducing swimming‐induced paralysis (SWIP). Expression of human DAT (hDAT wt ) in ce dat‐1 KO rescues SWIP defects, whereas dopamine transporter deficiency syndrome‐related mutations in hDAT (hDAT mut ) do not, or only partially, rescue the SWIP defects. We provide a new in vivo tool for investigating mutations in hDAT gene found in DTDS patients.